Association between anxiety and metabolic syndrome: An updated systematic review and meta-analysis - Ji, Shuang; Chen, Yujiao; Zhou, Yuying; Cao, Yiting; Li, Xiao; Ding, Guoyong; Tang, Fang (Frontiers in Psychiatry, 2023)
Objective: Previous studies have demonstrated an association between anxiety and metabolic syndrome (MetS). However, the association is still controversial. This updated meta-analysis aimed to reanalyze the association between anxiety and MetS. Methods: We comprehensively searched PubMed, Embase and Web of Science for all related studies published before January 23, 2023. Observational studies that informed effect size with 95% confidence interval (CI) for the association between anxiety and MetS were included. According to heterogeneity between studies, fixed or random effects models were applied to calculate the pooled effect size. Publication bias was examined by funnel plots. Results: The research included 24 cross-sectional studies: 20 studies used MetS as the dependent variable with a pooled OR of 1.07 (95% CI: 1.01-1.13) and 4 studies used anxiety as the dependent variable with a pooled OR of 1.14 (95% CI: 1.07-1.23). Three cohort studies were found: two studies detected the association of baseline anxiety with the risk of MetS, one of the studies demonstrated a significant association, but a similar result was not found in another study; one study showed no significant association between baseline MetS and the risk of anxiety. Conclusions: Cross-sectional studies indicated an association between anxiety and MetS. The results from cohort studies are still inconsistent and limited. More large-scale prospective studies are needed to further reveal the causal relationship of anxiety with MetS.